Species richness of Cladocera (Crustacea: Branchiopoda) in the Western Ghats of Maharashtra and Goa (India), with biogeographical comments - Sameer M. Padhye; Henri J. Dumont (Journal of Limnology, 2014)
We assessed the species richness of Cladocera of the Western Ghats and surrounding areas of Maharashtra and Goa. Data of 230 samples from about 80 localities collected between 2009 and 2013 revealed 51 species in six families. Non-parametric estimators of species richness, Chao 2 and Jackknife 2, estimated the real total at 58 and 63 species, suggesting a coverage of 80% of the total species of the area. This fauna was compared with that of other countries from the Oriental region and found to be relatively species-poor, which is not in line with the biodiversity rich area status of the Western Ghats. Reasons for this are unclear. Complementarity among the cladoceran faunas of different countries belonging to the Oriental region increased with latitude and altitude. Along with the complementarity index, a comparison of family and generic occurrences of Cladocera revealed that family-level representation was similar between countries but species occurrences (like Daphnia species) varied. The subgenus Daphnia was reported only from Nepal while Ctenodaphnia was common in all countries of the Indian region. Biogeographically, the fauna was mainly composed of wide-ranging tropical species, mixed with some rare Palaearctic elements. Only two species were endemic to India. Of another one, the closest relative lives in Yucatan, Mexico, and thus has a tropical Amphi-Pacific distribution.